Surface reinforcing agent for high-permeability concrete and preparation method of surface reinforcing agent
By adding specific components to the concrete surface reinforcement agent and adjusting the concentration compound, the problem of large differences in the use effect of concrete surface reinforcement agent in the prior art has been solved, which significantly improves the surface strength and durability of concrete, and improves a variety of performance indicators.
Patent Information
- Application Number
- CN202510024461.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-14
AI Technical Summary
The existing concrete surface reinforcement agent has components fixed, poor safety and environmental protection, and great differences in use effects, making it difficult to effectively improve the surface strength and durability of high-grade concrete.
It provides a surface reinforcement for high-permeability concrete, including potassium silicate, methyl silicate, nanosilica, polyvinyl acetate, styrene acrylic emulsion, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, dibutyl phthalate oil and polyester chain phosphate. By adjusting the concentration of the composite at the construction site according to the actual surface condition after the concrete is hardened, the permeability and film formation performance are improved.
It significantly improves the surface strength and durability of concrete, improves the hole structure and gap filling of concrete surface, improves the performance of high temperature resistance, electrical insulation, radiation resistance, flame retardant, waterproof and corrosion resistance, and is simple to operate, convenient to store, environmentally friendly and durable.
Smart Images

Figure CN119613012A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hardened concrete adjuvants, and in particular relates to a surface enhancer for high-permeability concrete and a preparation method thereof. Background Art
[0002] In modern construction projects, concrete is one of the main building materials, and its performance directly affects the quality and safety of the building. However, during the construction process, due to various reasons, such as quality problems of concrete raw materials and irregular construction, the concrete surface will have problems such as reduced strength, looseness and porosity, poor air tightness, and reduced durability. These problems not only affect the appearance, but more seriously affect the quality and safety of the building.
[0003] In the existing technologies for solving the above problems, generally, after the concrete has hardened, a finished liquid enhancer is evenly applied on its surface. However, these enhancers have fixed ingredients, poor safety and environmental protection, and especially large differences in use effects. For example, they are more effective for concrete with a lower design strength grade, while on the contrary, the surface strength increase of concrete with a higher grade is lower, and the actual use effect cannot be achieved. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned technologies, the present invention provides a surface enhancer for high-permeability concrete and a preparation method thereof, which uses environmentally friendly materials and adjusts and compoundes the concentration in a targeted manner according to the actual surface condition of the concrete after hardening at the construction site to solve the above-mentioned problems and achieve ideal use effects. A surface enhancer for high-permeability concrete includes the following mass concentration components: potassium silicate, methyl silicate, nano silicon dioxide, polyvinyl acetate, styrene acrylic emulsion, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, dibutyl phthalate oil, polyester chain phosphate, and the balance is water.
[0005] Wherein, the mass concentration of the potassium silicate when used is 150-300 g / L; the mass concentration of the methyl silicate when used is 20-50 g / L; and the mass concentration of the nano silicon dioxide when used is 30-60 g / L.
[0006] The mass concentration ratio of the polyvinyl acetate and styrene acrylic emulsion is 1:1, both of which are 5-10 g / L. Such substances can improve the penetration of silicates and silicon dioxide, reduce the porosity of the concrete surface, and significantly improve the surface strength and durability of the concrete.
[0007] The mass concentration of 2,2,4-trimethyl-1,3-pentanediol monomethyl ester when used is 2-5g / L; the mass concentrations of dibutyl phthalate oil and polyester chain phosphate ester when used are 0.5-2.5g / L and 3-9g / L respectively. When dibutyl phthalate oil and polyester chain phosphate encounter calcium hydroxide, a cement hydration product, during use, they release heat, so that the silicate and silicon dioxide nanoparticles that have been evenly dispersed can improve the pore structure of the concrete surface and repair microcracks through film formation. As a promoter, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester can accelerate the formation of film, improve the filling of gaps on the concrete surface, and improve high temperature resistance, electrical insulation, radiation resistance, flame retardancy, waterproofness and corrosion resistance.
[0008] The present invention also provides a method for preparing a surface enhancer for high permeability concrete, wherein the specific steps are as follows:
[0009] Step 1: Prepare potassium silicate powder by mixing disodium silicate and potassium sulfate and reacting them. The reaction product is dissolved, filtered, washed, dried, etc. to obtain potassium silicate powder, which is then collected for later use.
[0010] Step 2: Prepare modified silica. The silica raw material is crushed, mixed and screened to make it suitable for use in a gasification device. In the gasification device, the silica material is gasified by chlorosilane in a hydrogen-oxygen flame to generate gaseous silica molecules, which are polymerized into nanoparticles under specific conditions. The hydrophilic nano-silica powder is collected through gas-solid separation and post-treatment for use.
[0011] Step 3: The potassium silicate powder prepared in step 1, the modified silicon dioxide powder prepared in step 2, polyvinyl acetate, styrene acrylic emulsion, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, dibutyl phthalate oil, and polyester chain phosphate are uniformly mixed in a mass ratio to obtain a reinforcing agent powdery solid substance.
[0012] Step 4: The powdered mixture prepared in step 3 is uniformly mixed with the remaining water according to a mass ratio, and allowed to stand at 25±5°C for 24 hours to obtain a surface enhancer.
[0013] The specific conditions of step 1 are: drying temperature is 50-60° C. and time is 1-2 h.
[0014] The specific conditions of step 2 are as follows: the diameter of the silica is less than 100 nanometers after being crushed, and the conditions for polymerizing the nanoparticles are high pressure of 20 MPa and temperature of 2250-2300°C.
[0015] The beneficial effects of the present invention are as follows: compared with the prior art, the surface enhancer for high permeability concrete and the preparation method thereof provided by the present invention have the following advantages:
[0016] 1) The present invention adds polyvinyl acetate and styrene acrylic emulsion to the surface enhancer for high permeability concrete. Such substances can enhance the permeability of silicate and silicon dioxide, reduce the porosity of the concrete surface, and significantly improve the surface strength and durability of the concrete.
[0017] 2) The present invention adds 2,2,4-trimethyl-1,3-pentanediol monomethyl ester. 2,2,4-trimethyl-1,3-pentanediol monomethyl ester serves as a promoter to accelerate film formation, improve the filling of concrete surface gaps, and improve high temperature resistance, electrical insulation, radiation resistance, flame retardancy, waterproofness and corrosion resistance.
[0018] 3) When dibutyl phthalate oil and polyester chain phosphate encounter the cement hydration product calcium hydroxide during use, they will release heat, so that the already evenly dispersed silicate and silicon dioxide nanoparticles can form a film to improve the pore structure of the concrete surface and repair microcracks.
[0019] 4) The preparation method provided in the present application is simple to operate, convenient to store, and will not deteriorate easily, and is environmentally friendly and durable.
[0020] Figures and Description
[0021] Figure 1 The test results of the embodiments and comparative examples are shown. Specific embodiments
[0022] In order to more clearly describe the present invention, the present invention is further described below based on text and drawings. A surface enhancer for high permeability concrete includes the following components by mass concentration: potassium silicate, methyl silicate, nano silicon dioxide, polyvinyl acetate, styrene acrylic emulsion, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, dibutyl phthalate oil, polyester chain phosphate, and the balance is water.
[0023] In this embodiment, the mass concentration of the potassium silicate when used is 150-300 g / L; the mass concentration of the methyl silicate when used is 20-50 g / L; and the mass concentration of the nano-silicon dioxide when used is 30-60 g / L.
[0024] In this embodiment, the mass concentration ratio of the polyvinyl acetate and styrene acrylic emulsion is 1:1, both of which are 5-10 g / L.
[0025] In this embodiment, the mass concentration of the 2,2,4-trimethyl-1,3-pentanediol monomethyl ester when used is 2-5 g / L; the mass concentrations of the dibutyl phthalate oil and the polyester chain phosphate ester when used are 0.5-2.5 g / L and 3-9 g / L respectively.
[0026] The present invention also provides a method for preparing a surface enhancer for high permeability concrete, wherein the specific steps are as follows:
[0027] Step 1: Prepare potassium silicate powder by mixing disodium silicate and potassium sulfate and reacting them. The reaction product is dissolved, filtered, washed, dried, etc. to obtain potassium silicate powder, which is then collected for later use.
[0028] Step 2: Prepare modified silica. The silica raw material is crushed, mixed and screened to make it suitable for use in a gasification device. In the gasification device, the silica material is gasified by chlorosilane in a hydrogen-oxygen flame to generate gaseous silica molecules, which are polymerized into nanoparticles under specific conditions. The hydrophilic nano-silica powder is collected through gas-solid separation and post-treatment for use.
[0029] Step 3: The potassium silicate powder prepared in step 1, the modified silicon dioxide powder prepared in step 2, polyvinyl acetate, styrene acrylic emulsion, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, dibutyl phthalate oil, and polyester chain phosphate are uniformly mixed in a mass ratio to obtain a reinforcing agent powdery solid substance.
[0030] Step 4: The powdered mixture prepared in step 3 is uniformly mixed with the remaining water according to a mass ratio, and allowed to stand at 25±5°C for 24 hours to obtain a surface enhancer.
[0031] In this embodiment, the specific conditions of step 1 are: the drying temperature is 50-60° C. and the drying time is 1-2 h.
[0032] In this embodiment, the specific conditions of step 2 are: the diameter of the silica is less than 100 nanometers after being crushed, and the conditions for polymerizing nanoparticles are high pressure of 20 MPa and temperature of 2250-2300°C.
[0033] The beneficial effects of the present invention are as follows: compared with the prior art, the surface enhancer for high permeability concrete and the preparation method thereof provided by the present invention have the following advantages:
[0034] 1) The present invention adds polyvinyl acetate and styrene acrylic emulsion to the surface enhancer for high permeability concrete. Such substances can enhance the permeability of silicate and silicon dioxide, reduce the porosity of the concrete surface, and significantly improve the surface strength and durability of the concrete.
[0035] 2) The present invention adds 2,2,4-trimethyl-1,3-pentanediol monomethyl ester. 2,2,4-trimethyl-1,3-pentanediol monomethyl ester serves as a promoter to accelerate film formation, improve the filling of concrete surface gaps, and improve high temperature resistance, electrical insulation, radiation resistance, flame retardancy, waterproofness and corrosion resistance.
[0036] 3) When dibutyl phthalate oil and polyester chain phosphate encounter the cement hydration product calcium hydroxide during use, they will release heat, so that the already evenly dispersed silicate and silicon dioxide nanoparticles can form a film to improve the pore structure of the concrete surface and repair microcracks.
[0037] 4) The preparation method provided in the present application is simple to operate, convenient to store, and will not deteriorate easily, and is environmentally friendly and durable.
[0038] Unless otherwise specified, the methods used in this embodiment are conventional data testing standards known to those skilled in the art, including rebound value and wear resistance testing.
[0039] Rebound value: Refer to the standard method of "Technical Specification for Testing Concrete Compressive Strength by Rebound Method JGJ / T23-2001" to test the rebound strength of 0d+7d+56d.
[0040] Durability test: Cut the concrete into concrete specimens with a diameter of 100 mm and a height of 50 mm, and test the chloride ion permeability of the concrete according to the standard GB / T50082-2009 "Standard for test methods of long-term performance and durability of ordinary concrete". Chloride ion permeability indicates the rate at which chloride ions penetrate into the concrete, which is expressed by the chloride ion diffusion coefficient.
[0041] Abrasion resistance test: refer to the standard GB / T 16925-1997 "Test method for abrasion resistance of concrete and its products", the specimen size is 100mm×100mm×100mm.
[0042] Example 1
[0043] Potassium silicate 225g / L, methyl silicate 35g / L; nano silicon dioxide 45g / L, polyvinyl acetate 7.5g / L, styrene acrylic emulsion 7.5g / L, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester 3.5g / L, dibutyl phthalate oil 1.5g / L, polyester chain phosphate 6g / L.
[0044] The test results of Example 1 are as follows: the rebound strength 0d is 43.9, 7d is 49.1, 56d is 50.3; the chlorine resistance (electric flux) is 1050; and the wear resistance is 4.7.
[0045] Example 2
[0046] Potassium silicate 150g / L, methyl silicate 20g / L; nano silicon dioxide 30g / L, polyvinyl acetate 5g / L, styrene acrylic emulsion 5g / L, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester 2g / L, dibutyl phthalate oil 0.5g / L, polyester chain phosphate 3g / L.
[0047] The test results of Example 2 are as follows: the rebound strength 0d is 44.1, 7d is 50.9, 56d is 51.3; the chlorine resistance (electric flux) is 1029; and the wear resistance is 4.7.
[0048] Example 3
[0049] Potassium silicate 300g / L, methyl silicate 50g / L; nano silicon dioxide 60g / L, polyvinyl acetate 10g / L, styrene acrylic emulsion 10g / L, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester 5g / L, dibutyl phthalate oil 2.5g / L, polyester chain phosphate 9g / L.
[0050] The test results of Example 3 are as follows: the rebound strength 0d is 43.9, 7d is 52.5, and 56d is 53.4; the chlorine resistance (electric flux) is 1075; and the wear resistance is 4.4.
[0051] Comparative Example 1
[0052] Potassium silicate 225g / L, methyl silicate 35g / L; nano silicon dioxide 45g / L, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester 3.5g / L, dibutyl phthalate oil 1.5g / L, polyester chain phosphate 6g / L.
[0053] Comparative Example 1 lacks polyvinyl acetate and styrene acrylic emulsion compared to Example 1, and the test results obtained are rebound strength 0d is 43.8, 7d is 45.1, 56d is 45.6, chlorine resistance (electric flux) number is 1249; wear resistance is 3.5.
[0054] Comparative Example 2
[0055] Potassium silicate 225g / L, methyl silicate 35g / L; nano silicon dioxide 45g / L, polyvinyl acetate 7.5g / L, styrene acrylic emulsion 7.5g / L, 3.5g / L, dibutyl phthalate oil 1.5g / L, polyester chain phosphate 6g / L.
[0056] Compared with Example 1, Comparative Example 2 lacks 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, and the test results are as follows: the rebound strength 0d is 44.1, 7d is 46.1, 56d is 47.3; the chlorine resistance (electric flux) is 1179; and the wear resistance is 3.4.
[0057] Comparative Example 3
[0058] Potassium silicate 225g / L, methyl silicate 35g / L; nano silicon dioxide 45g / L, polyvinyl acetate 7.5g / L, styrene acrylic emulsion 7.5g / L, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester 3.5g / L, dibutyl phthalate oil 1.5g / L, polyester chain phosphate 6g / L.
[0059] Compared with Example 1, Comparative Example 3 lacks dibutyl phthalate oil and polyester chain phosphate. The test results are as follows: the rebound strength 0d is 44.5, 7d is 45.9, 56d is 46.3; the chlorine resistance (electric flux) is 1296; and the wear resistance is 3.7.
[0060] Conclusion: From the above data, it can be seen that the high permeability concrete surface enhancer obtained by the complete use of the formula of this application, such as Figure 1 It can be seen from the description that after the results of Example 1, Example 2, and Example 3 are used, the rebound strength is significantly improved, and it is basically stable after one week; the anti-chlorine flux is not higher than 1110, and the wear resistance is significantly improved to above 4.4; in the comparative example, compared with Example 1, Comparative Example 1 lacks polyvinyl acetate and styrene acrylic emulsion, and the test results obtained are rebound strength 0d is 43.8, 7d is 45.1, 56d is 45.6, and the anti-chlorine (electric flux) number is 1249; wear resistance is 3.5, and Comparative Example 2 lacks 2,2,4-trimethylol -1,3-pentanediol monomethyl ester, the test results are rebound strength 0d is 44.1, 7d is 46.1, 56d is 47.3; chlorine resistance (electric flux) is 1179; wear resistance is 3.4, compared with Example 1, comparative example 3 lacks dibutyl phthalate oil and polyester chain phosphate, and the test results are rebound strength 0d is 44.5, 7d is 45.9, 56d is 46.3; chlorine resistance (electric flux) is 1296; wear resistance is 3.7, in the comparative example, the chlorine resistance electric flux is significantly improved by more than 1150, while the wear resistance is less than 4, and the degree of improvement in rebound strength is low.
[0061] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a super permeable concrete surface enhancer and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments. The various specific technical features described in the above-mentioned specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. It should be clear to those skilled in the art that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A surface enhancer for high permeability concrete, characterized in that: The invention comprises the following components in mass concentration: potassium silicate, methyl silicate, nano silicon dioxide, polyvinyl acetate, styrene acrylic emulsion, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, dibutyl phthalate oil, polyester chain phosphate, and the balance is water.
2. A surface enhancer for high permeability concrete according to claim 1, characterized in that: The mass concentration of the potassium silicate when in use is 150-300 g / L; the mass concentration of the methyl silicate when in use is 20-50 g / L; and the mass concentration of the nano silicon dioxide when in use is 30-60 g / L.
3. A surface enhancer for high permeability concrete according to claim 1, characterized in that: The mass concentration ratio of the polyvinyl acetate and styrene acrylic emulsion when used is 1:1, both of which are 5-10 g / L.
4. A surface enhancer for high permeability concrete according to claim 1, characterized in that: The mass concentration of the 2,2,4-trimethyl-1,3-pentanediol monomethyl ester when used is 2-5 g / L; the mass concentrations of the dibutyl phthalate oil and the polyester chain phosphate ester when used are 0.5-2.5 g / L and 3-9 g / L respectively.
5. A method for preparing a surface enhancer for high permeability concrete, characterized in that: The specific steps are as follows: Step 1: Prepare potassium silicate powder by mixing disodium silicate and potassium sulfate and reacting them. The reaction product is dissolved, filtered, washed, dried, etc. to obtain potassium silicate powder, which is then collected for later use. Step 2: Prepare modified silica. The silica raw material is crushed, mixed and screened to make it suitable for use in a gasification device. In the gasification device, the silica material is gasified by chlorosilane in a hydrogen-oxygen flame to generate gaseous silica molecules, which are polymerized into nanoparticles under specific conditions. The hydrophilic nano-silica powder is collected through gas-solid separation and post-treatment for use. Step 3: The potassium silicate powder prepared in step 1, the modified silicon dioxide powder prepared in step 2, polyvinyl acetate, styrene acrylic emulsion, 2,2,4-trimethyl-1,3-pentanediol monomethyl ester, dibutyl phthalate oil, and polyester chain phosphate are uniformly mixed in a mass ratio to obtain a reinforcing agent powdery solid substance. Step 4: The powdered mixture prepared in step 3 is uniformly mixed with the remaining water according to a mass ratio, and allowed to stand at 25±5°C for 24 hours to obtain a surface enhancer.
6. According to claim 5, the method for preparing a surface enhancer for high permeability concrete is characterized in that: The specific conditions of step 1 are: drying temperature is 50-60° C. and time is 1-2 h.
7. According to claim 5, the method for preparing a surface enhancer for high permeability concrete is characterized in that: The specific conditions of step 2 are: the diameter of the silica is less than 100 nanometers after being crushed, and the conditions for polymerizing nanoparticles are high pressure 20 MPa and temperature 2250-2300°C.